Nineveh Overturned: Augustine and Chrysostom on the Threat of Jonah - Hannan, Sean ca. 20./21. Jh. (Journal of early Christian studies, 2020)
Both John Chrysostom and Augustine of Hippo find in the story of Jonah and the Ninevites an invitation to reflect upon the moral and political challenges undergone by cities facing the possibility of disaster. While Nineveh was threatened with destruction at the hands of the divine, cities like Constantinople and Rome were instead threatened with disaster of a natural or military kind, ranging from earthquakes to invasions. Regardless, both Chrysostom and Augustine thought the lessons of Jonah could be applied to contemporary crises. The two pastoral preachers did so in quite different ways, however. For Chrysostom, the repentance of the Ninevites in the face of a divine threat served as a model for his own congregation. For Augustine, however, the divine was incapable of uttering threats, and so Jonah's prophecy had to come true: Nineveh had to be overturned. In order to make this case, Augustine reconfigured the meaning of the word "overturning" (euersio), so that he could make the case that the repentance of the Ninevites was driven not by their fear, but rather by the combined agency of divine grace and political coercion.